Impact of infrastructure expenses in strategic sectors for Brazilian poverty - Emerson Marinho; Guaracyane Campelo; Jo\~ao França; Jair Araujo (EconomiA, 2017)
This paper analyzes the impact of infrastructure investments in the reduction of poverty in Brazil, controlled through other determinants such as economic growth, income inequality, average schooling years, unemployment rate and state budgets from 1995 to 2011. A model for a dynamic panel data, estimated by the generalized method of moments (GMM) in two steps as developed by Arellano-Bond (1991) and Blundell-Bond (1998) found among other conclusions, a significant inverse relation between public investment in infrastructure and poverty. The Granger causality test for panel data proposed by Hurlin and Venet (2001, 2004) and Hurlin (2004, 2005) reinforced results validation. – – O trabalho tem como objetivo principal analisar o impacto dos investimentos em infraestrutura nos setores estratégicos da economia (transporte, energia, comunicaç\~ao, saúde e saneamento) na reduç\~ao da pobreza controlando por outros determinantes tais como crescimento econômico, desigualdade de renda, anos médio de estudo, taxa de desemprego e receitas governamentais orçamentárias para os estados brasileiros, no período de 1995 a 2011. Um modelo para dados em painel dinâmico, estimado pelo método de momentos generalizados-sistema (MMG-S) em dois passos, desenvolvido por Arellano-Bond (1991) e Blundel-Bond (1998), detectou, entre outras conclus\~oes, uma relaç\~ao significante entre os investimentos públicos em infraestrutura e pobreza, sendo estes uma ferramenta eficiente no combate desta. Os outros determinantes investigados desempenham um papel importante na dinâmica da pobreza no Brasil. O teste de causalidade de Granger para dados em painel, proposto por Hurlin e Venet (2001, 2004) e Hurlin (2004, 2005) valida os resultados."
Keywords: 330; Poverty; Infrastructure; Dynamic panel; Pobreza; Infraestrutura; Painel dinâmico